The linguistic features of Bangala before Lingala: The pidginization of Bobangi in the 1880s and 1890s - Meeuwis, Michael (AAeO - Afrikanistik-Aegyptologie-Online, 2019)
Described are the lexical and grammatical features of the pidgin Bangala, spoken between roughly 1880 and 1900 in western, northern, and northeastern Congo. This pidgin formed the basis of what after 1900 became, in northern and western Democratic Republic of the Congo, Lingala, and what in northeastern DRC remained known as “Bangala”. Pre 1900 Bangala arose out of the pidginization of Bobangi in the context of the arrival of the first European conquerors and their East and West African troops. First is discussed the sociohistorical evidence given by contemporaneous sources for the emergence of Bangala out of Bobangi and its development then into Lingala. The problematic notions of “pidgin” and “pidginization” is also addressed. The bulk of the article then describes the linguistic features of the pidgin. This is done on the basis of contemporaneous sources, documenting the lan¬guage as it was spoken in its own time, and on the basis of strict data selection criteria. The linguistic features of the pidgin included, in the lexicon, the loss of the functional load of tone, the scarcity of function words, word category indeterminacy through generalization and multi¬functionality, foreign input, and more than average use of transparent periphrasis; and, in the grammar, reduction of nominal class inflection and of agreement patterns in the noun phrase, reduction in subject person inflection on the verb, reduction of tense aspect modality distinctions, loss or reduction of root ex¬tensions, and a strong general tendency away from morphological syntheticity towards syntactic ana¬lyticization. The study of the colonial context and of the linguistics of pre 1900 Bangala is of major importance for our understanding of present day Lingala and northeastern Bangala.